HUBUNGAN ANTARA HARDINESS DENGAN BURNOUT PADA SANTRI PONDOK PESANTREN PERSATUAN ISLAM PUTRA BANGIL - Abd Rochman Fahmi; Widyastuti (Jurnal Psikologi Poseidon, 2018)
Density of boarding activities demanding students to do more intense routines. These routines can be a pressure for students that experienced mental fatigue of Burnout. Burnout can be affected by external factors or internals. Internals factors become very important because individual assessnebt against external factors depend on its internal factors. The method of this research is quantitative correlational by using the boarding school’s students as subjects. Determination of the subject use proporsionate stratified random sampling. The method of data collection is spread the questioner wich contain Hardiness and Burnout scale based on aspects of each variables. This research analyze the relationship of Hardiness as internal factor with Burnout on boarding school’s students. This research use quantitative correlational method with a scale of Hardiness and Burnout that distribute on 97 boarding school’s students. The result of this research are calculated using the correlational product moment, then obtained a very significant result with a value of correlational is – 0,714. Based on the result , the correlation between Hardiness and Bunrout has proven with a negative direction of hypothesis. Based on simple regression analysis on the results, obtained F of 92,664 with sig = 0.000 which sig is less than 0.05. The effective contribution of Hardiness against Burnout is 50.5%, the meaning there is still a 49.5% chance of Burnout is affected by other variables.